To solve the inequality \( 25m - 7 \leq 17 \), we will follow two steps. I'll justify each step using properties of inequalities.

### Step 1: Add 7 to both sides

**Justification:**
When we add (or subtract) the same number to both sides of an inequality, the direction of the inequality remains the same.

Here, we add 7 to both sides:

\[
25m - 7 + 7 \leq 17 + 7
\]

This simplifies to:

\[
25m \leq 24
\]

### Step 2: Divide both sides by 25

**Justification:**
When we divide (or multiply) both sides of an inequality by a positive number, the direction of the inequality remains the same.

Now, we divide both sides by 25:

\[
\frac{25m}{25} \leq \frac{24}{25}
\]

This simplifies to:

\[
m \leq \frac{24}{25}
\]

### Conclusion
So, the solution to the inequality \( 25m - 7 \leq 17 \) is:

\[
m \leq \frac{24}{25}
\]

This completes the justification for both steps in solving the inequality using the properties of inequalities.

MAKE THIS LIKE A 6TH GRADER WROTE IT

1 answer

To solve the inequality \( 25m - 7 \leq 17 \), we can break it down into two easy steps. I'll explain why I do each step!

Step 1: Add 7 to both sides

Why I can do this: When you add (or take away) the same number from both sides of an inequality, it doesn't change the story; the inequality sign stays the same.

So, I add 7 to both sides like this:

\[ 25m - 7 + 7 \leq 17 + 7 \]

Now, let’s simplify it! The left side becomes:

\[ 25m \quad (\text{because } -7 + 7 = 0) \]

And the right side becomes:

\[ 17 + 7 = 24 \]

So now we have:

\[ 25m \leq 24 \]

Step 2: Divide both sides by 25

Why I can do this: When we divide (or multiply) both sides of an inequality by a positive number, it also doesn’t change the direction of the inequality.

Now I divide both sides by 25:

\[ \frac{25m}{25} \leq \frac{24}{25} \]

This simplifies to:

\[ m \leq \frac{24}{25} \]

Conclusion

So, the solution to the inequality \( 25m - 7 \leq 17 \) is:

\[ m \leq \frac{24}{25} \]

And that’s how we solve the inequality step by step!